One And Inseparable Armenian Nation, One And Inseparable Armenian Culture - Bekaryan, Anahit (ՀՀ ԳԱԱ «Գիտություն» հրատ.)
In 1967, the Constantinople Armenians in Montreal established the Expatriates’ Union. Free from all kinds of political, religious, and party affiliations, it stands out as the most liberal and devoted advocate of the Armenian traditions. Since 1969, the Union of Constantinople Armenians has owned its own theatre hall, dedicated to hosting performances in Armenian. The inaugural cultural event took place on April 12, 1969, quickly gaining popularity among Armenians in Montreal. Since the early days of the Union, former graduates of Mkhitarian, Esayan, and Kedronakan Colleges have been actively engaged in the cultural committee, working for the benefit of the nation. Through their dedication and initiative, the cultural body “MEK” of the Union of Constantinople Armenians was established in 1973, named after the initials of the schools. The MEK cultural body operates under the slogan “MEK and inseparable Armenian nation, MEK and inseparable culture”. The Union of Constantinople Armenians has been active for more than fifty years, remaining dedicated to its mission: “to serve the unified Armenian nation and its culture.” Մոնրեալում հաստատված պոլսահայերի ջանքերով 1967-ին ստեղծվել է Պոլսահայ հայրենակցական միությունը, որը դարձել է հայկական ավանդույթների ջատագովն ու հավատարիմ պաշտպանը: 1969-ին միությունը ունեցավ իր սեփական շենք կենտրոնը, որի թատերասրահում կազմակերպվում են գեղարվեստական երեկոներ և թատերական ներկայացումներ: Պոլսահայ միությունում գործող թատերախումբը մեծ ժողովրդականություն է վայելում մոնրեալահայերի մոտ: Ավելի քան հիսուն տարի գործող Պոլսահայ միությունը, շարունակում է լինել գործակցության և միասնական ոգու ջահակիր: Усилиями обосновавшихся в Монреале константинопольских армян в 1967 году был создан Земляческий союз константинопольских армян, став-ший поборником и верным защитником армянских традиций. С 1969 года Союз константинопольских армян приобрел здание, в театральном зале которого регулярно организуются художественные вечера и театральные представления на армянском языке. При Союзе константино-польских армян действует театральная труппа, пользующаяся популярностью среди монреальских армян. На протяжении более 50 лет Союз константино-польских армян играет консолидирующую роль в монреальской армянской общине, пропагандируя армянскую культуру.
Keywords: Art